Energy efficiency in urban public lighting: literature review of equipment and technologies (Research, Society and Development, 2020)
With the increase in population and the need for greater amounts of natural resources to meet all the world's energy demand, the search for sustainable use of these resources is essential. One way to achieve this is through energy efficiency. Thus, this paper presents and compares the main existing resources for improving energy efficiency in urban public lighting, through bibliographic and documentary research. At the same time, energy efficiency programs in Brazil and incentives promoted by government-related institutions are cited. Finally, current technologies are demonstrated with case studies that aim to promote the energy efficiency of urban street lighting, highlighting their advantages and disadvantages. As a result, it is identified that the most viable alternative for revitalizing the street lighting system is the retrofit of traditional lamps by LED lamps, as it is a feature with greater durability, lower power consumption and less need for network adaptations. electrical current. However, from retrofit with LED lamps, it is possible to deploy additional features and technologies that allow intelligent monitoring of the entire system, adding, in addition to greater energy savings, more safety for the population.